Seleção de tratores agrícolas adequados à agricultura familiar. - Andersson, Norberto Luiz Marques (2010)
Family-based farmers work in their fields primarily with crops that can ensure their livelihood. For this reason, they make use of both creativity and the resources available in the farm in order to make their job easier and reduce costs, taking advantage of crop diversification as a necessary action for their food security. As new resources compatible with their savings become available through government lines of credit, farmers can technicize their properties mainly through the acquisition of tractors and agricultural machinery to facilitate and expedite their work. With the aim of supporting these farmers to acquire agricultural tractors suitable for their needs, an assisting and supporting decision methodology based on technical criteria, costs, ergonomics and safety has been developed. Data from 30 families who bought new tractors through PRONAF (National Programme to foster family and small scale farmers) informed this methodology. Next, it was made a comparing spreadsheet between the criteria established with the multicriteria methodology and those directly measured from the tractors purchased by this group of farmers. The results obtained allowed to infer that the model and the spreadsheet established in this work can be easily adapted to other situations and regions where there is the tendency to mechanicize the work of agricultural mechanization. It was also found that low-power but affordable tractors to purchase, as well as operational cost items consistent with the capacity of the tractor, seem to be extremely important for the families surveyed.